The influence of mindfulness on employees’ resilience at Eskom, Northern Cape - Motaung, Mophomotseng Millicent (University of the Free State, 2023)
International trends such as globalisation, epidemics, and rapid technological developments impact individuals locally and internationally on all levels of society, with electricity companies experiencing increased challenges. The various challenges and stressful working conditions lead to employees experiencing exhaustion when trying to cope with the demanding work environment. Therefore, resilience, defined as one’s capability to adapt to changes, adhere to, and accomplish objectives despite existing challenges, is necessary for survival in such a turbulent environment. For Kelly et al. (2019), mindfulness is the antidote to resilience. Mindfulness is one of the individual qualities advocated to assist employees in properly managing psychological stress in the workplace and is a critical psychological resource for improving employee performance. Thus, mindfulness can be viewed as a unique personal feature of employees that protects them from negative emotions connected with a demanding workload and stressful work conditions, thereby reducing emotional tiredness. Therefore, this study aimed to determine if mindfulness influences employees’ resilience at Eskom, Northern Cape (NC). The study also aimed to determine if a relationship exists between mindfulness and resilience among employees at Eskom, NC. Lastly, using a non-experimental research design, the study aimed to determine if gender differences exist in career resilience among employees at Eskom, NC. A non-experimental quantitative survey research design was utilised to obtain the data from employees at Eskom (a large electricity company) in Northern Cape, South Africa (SA). Questionnaires used to obtain the data included the demographic questionnaire, the Adult Resilience Indicator (ARI) questionnaire, and the Mindfulness Attention Awareness Scale (MAAS) questionnaire. Data was analysed using regression analyses, correlational analyses and the t-test for independent groups. The results indicated that mindfulness positively influences career resilience. Furthermore, the results indicated no significant differences in resilience in terms of gender. The study thus provides new knowledge on the relationship between mindfulness and resilience. It also presents the rationale for implementing mindfulness training in organisations to assist employees in positively adapting to the pressures experienced by electricity companies in South Africa.
Dissertation(MBA (Business Administration))--University of the Free State, 2023
Keywords: Resilience; Mindfulness; Protective factors; Risk factors; Resources; Assets; Risk employee well-being; Stress; Gender; Age